Pelatihan Manajemen Koperasi Dan Aplikasi Microsof Office Bagi Pengurus Koperasi Simpan Pinjam PKH Wirun Wijaya, Kecamatan Mojolaban, Kabupaten Sukoharjo - Novemy Triyandari Nugroho; Rudi Susanto; Wiji Lestari (Universitas Muria Kudus, 2019)
The purpose of this community service activity is to provide training in the principles of koperasi management and training in the use of microsof office for bookkeeping of koperasi. Partner in this activity is KSP PKH Wirun Wijaya. The stages of training used are preparation of materials and schedules, equipment preparation, training and evaluation. The results of this activity are 1) The average percentage increase in the value of participants compared to the pre-test value on management aspects and information technology aspects is 41.31%; 2) Training participants are able to understand the principles of koperasi management and are able to use information technology, especially using microsof office software in conducting koperasi bookkeeping